1999
DOI: 10.1063/1.123540
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-density atomic force microscopy data storage with erase capability

Abstract: We report a simple atomic force microscopy-based concept for a hard disk-like data storage technology. Thermomechanical writing by heating a Si cantilever in contact with a spinning polycarbonate disk has already been reported. Here the medium has been replaced with a thin polymer layer on a Si substrate, resulting in significant improvements in storage density. With this new medium, we achieve bit sizes of 10-50 nm, leading to data densities of 500 Gbit/in. 2 . We also demonstrate a novel high-speed and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
165
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(170 citation statements)
references
References 11 publications
(4 reference statements)
0
165
0
1
Order By: Relevance
“…7. Binnig et al 5 demonstrated a data density of 400 Gb/in. 2 by writing thermomechanical data bits of diameter 40 nm in a poly-methylmethacrylate ͑PMMA͒ layer of thickness 40 nm.…”
Section: Atomic Force Microscope Cantilevers For Combined Thermomechamentioning
confidence: 99%
See 3 more Smart Citations
“…7. Binnig et al 5 demonstrated a data density of 400 Gb/in. 2 by writing thermomechanical data bits of diameter 40 nm in a poly-methylmethacrylate ͑PMMA͒ layer of thickness 40 nm.…”
Section: Atomic Force Microscope Cantilevers For Combined Thermomechamentioning
confidence: 99%
“…[3][4][5] The same cantilever can be used to detect the presence of a previously written data bit. 5 As the cantilever tip follows the contour of a data bit, the reduction in thermal impedance between the cantilever and the substrate causes a lower temperature rise in the heated cantilever, also shown in Fig. 1.…”
Section: Atomic Force Microscope Cantilevers For Combined Thermomechamentioning
confidence: 99%
See 2 more Smart Citations
“…The widespread use of thin films in a range of applications and industries, from coatings, inks and lithography to nano-imprinting, optoelectronics, and memory devices 1 , has made the understanding of thin films, particularly the changes induced by structural relaxation and solvent evaporation, very important. There is a need to know if a film will change in dimensions after its deposition and how fast these changes will occur.…”
Section: Solvent Lossmentioning
confidence: 99%